Impact : vol. 1, no. 1, April, 1943. - United States. Army Air Forces (Washington, D. C. : Office of the Assistant Chief of Air Staff, Intelligence, 1943)
In a recent conference with General Arnold I suggested that the value of classified aerial photography could be increased if disseminated in a regular manner. I recommended that the Army Air Forces publish a periodical devoted mainly to photographic portrayal of the methods and results of our operations, so that Air Force units and the Army as a whole might be kept informed of current developments. General Arnold heartily approved and thus was born Impact. Table of Contents: North African Targets; Ships Can Be and Are Hit; Our First Air-Borne Invasion; Precision in Burma; Attacks on Sub Bases; Industrial Targets; Zeke, Hap & Oscar; Bombs for Japs in China; Minimum Altitude Bombing; Combat in Iceland; Dummy Planes; Kiska, Familiar Target; Tailess Wonder.